Pengembangan Potensi Objek Wisata Pasar Van Der Capellen Berdasarkan Perspektif Collaborative Governance - Natasya Vadella; Nora Eka Putri (Jurnal Teori dan Riset Administrasi Publik, 2022)
Abstract This study aims to describe the potential development of the Van Der Capellen Market Tourism Object in Batusangkar City based on the Collaborative Governance perspective. This research is motivated by the existence of the Van Der Capellen Market as a new tourist attraction which was inaugurated in 2018. In the development of the Van Der Capellen Market, there are several parties involved, namely the local government, the GenPi organization and the community. With the involvement of various parties, this becomes a collaboration in the development of the Van Der Capellen Market tourist attraction. With the collaboration or cooperation carried out as well as support from various parties, it is hoped that the efforts to develop the Van Der Capellen Market Tourism Object can run properly. So that this tourist attraction can develop well and can be known by many people. This study uses a descriptive quasi-qualitative method. As a result, the collaboration carried out in the potential development of the Van der Capellen Market Tourism Object went well because the government and the community strongly supported the existence of the market. However, it is undeniable that in this development effort there are constraints due to budgetary funds so that the construction is not yet fully prepared. It is hoped that the government and related parties will further support the development of this market, so that this tourism object can develop well and also that people who sell tourism objects and local residents can be helped economically by this market.